Body Image Relationships, Physical Activity And Balanced Nutrition Knowledge With Adolescent Nutrition Status In Budi Murni 2 Medan High School - irfan said; Tuty Hertati Purba; Hermawati Hamalding; Royanti elida sidabutar (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Nutritional Status is a state of the body due to consuming food and the use of nutritional substances. Nutritional status is differentiated into three namely lack of nutritional status, good nutritional status, and more nutritional status. Determining the nutritional status of teenagers can be done in several ways one of them by using the body's time index. The rate of obesity in children and adolescents in the world, increased from less than 1 percent (the equivalent of five million girls and six million boys) in 1975, became almost 6 percent in girls (50 million) and almost 8 percent in boys (74 million) in the year 2016. This type of research is an observational research with a cross sectional study design that is a study where data collection is taken at the same time. Samples were taken using proportional random sampling. Univariate and bivariate data analysis using Chisquare. The results showed that all the variables studied were related to the adolescent nutritional status at Budi Murni 2 Medan High School with a value of P = (< 0.05). The conclusion of this research is body image, physical activity and nutritional knowledge related to adolescent nutritional status in Budi Murni 2 Medan High school year 2019. The advice in this study is that students are diligent in activities such as exercise and reduce excess food intake into the body to help keep the body shape proportional and normal nutritional status.